Antimicrobial resistance among common bacterial pathogens in Indonesia: a systematic reviewResearch in context - Michael W. Gach; Gilbert Lazarus; Daniel Martin Simadibrata; Robert Sinto; Yulia Rosa Saharman; Ralalicia Limato; Erni J. Nelwan; H. Rogier van Doorn; Anis Karuniawati; Raph L. Hamers (Elsevier, 2024)
Summary: Background: The WHO Global Antimicrobial Resistance Surveillance System (GLASS) aims to describe antimicrobial resistance (AMR) patterns and trends in common bacterial pathogens, but data remain limited in many low and middle-income countries including Indonesia. Methods: We systematically searched Embase, PubMed and Global Health Database and three Indonesian databases for original peer-reviewed articles in English and Indonesian, published between January 1, 2000 and May 25, 2023, that reported antimicrobial susceptibility for the 12 GLASS target pathogens from human samples. Pooled AMR prevalence estimates were calculated for relevant pathogen-antimicrobial combinations accounting for the sampling weights of the studies (PROSPERO: CRD42019155379). Findings: Of 2182 search hits, we included 102 papers, comprising 19,517 bacterial isolates from hospitals (13,647) and communities (5870). In hospital settings, 21.6% of Klebsiella pneumoniae isolates, 18.3% of Escherichia coli isolates, 35.8% of Pseudomonas aeruginosa isolates and 70.7% of Acinetobacter baumannii isolates were carbapenem-resistant; 29.9% of Streptococcus pneumoniae isolates were penicillin-resistant; and 22.2% of Staphylococcus aureus isolates were methicillin-resistant. Hospital prevalence of carbapenem-resistant K. pneumoniae and E. coli, and penicillin-resistant S. pneumoniae increased over time. In communities, 28.3% of K. pneumoniae isolates and 15.7% of E. coli isolates were carbapenem-resistant, 23.9% of S. pneumoniae isolates were penicillin-resistant, and 11.1% of S. aureus isolates were methicillin-resistant. Data were limited for the other pathogens. Interpretation: AMR prevalence estimates were high for critical gram-negative bacteria. However, data were insufficient to draw robust conclusions about the full contemporary AMR situation in Indonesia. Implementation of national AMR surveillance is a priority to address these gaps and inform context-specific interventions. Funding: Wellcome Africa Asia Programme Vietnam.